Variação e preconceito linguístico: uma discussão com os alunos de letras da UEPG e suas atitudes perante o currículo. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
In 2015, the State University of Ponta Grossa (UEPG) changed the Language and Literature courses’ curriculum. With that, it provided to the graduate a bigger autonomy to choose the subjects which were more interesting to them. Therefore, our paper has as general goal to analyze the students’ attitudes toward the current curriculum and as specific goals to verify the students’ main difficulties and to give some suggestions to curriculum improvement. Therefore, we deal with some concepts concerning our study. Firstly, we start with the language conception which will guide the study. Some authors were used, such as: BOURDIEU ([1977] 1983); CALVET (2002); BAGNO (2007); FIGUEIREDO NETO (2016). Then, we make a historic recovery about Sociolinguistics, in order to help us in our task we count on authors like: WEINREICH, LABOV, HERZOG ([1975] 2006); ECKERT (2012); CAMACHO (2013); MOREIRA e SILVA (2015); MOTA e SILVA (2019). In addition, we deal with linguistic variation and prejudice with the support of the following authors: FARACO (2008; 2011; 2015); CARDOSO (2010); BAGNO (2014); FIGUEIREDO NETO (2016); SILVA, BOTELHO, FERNANDES (2019). Finally, we conceptualize attitudes with the support of the authors like: LAMBERT, LAMBERT (1981); SILVA-CORVALÁN (1989); LOPÉZ MORALES (1993); BOTASSINI (2013). Then, we presented UEPG’s Language and Literature courses new curriculum, as well as its conceptions. We go then to the research methodology which were performed in three parts: first, we applied a questionnaire to raise the socioeconomic profile of the participants, after that we asked them to write up a report about some menus previously chosen. Finally, the participants were interviewed individually. As a result, we concluded: a) the Language and Literature course’s current curriculum really provides to the student a bigger autonomy; b) the students’ attitudes towards the curriculum vary between positives and negatives depending on some factors like: their expectation with the course, the professor who ministered the subject and the student’s field of interest.
Keywords: Atitudes; Sociolinguística; Currículo; Attitudes; Sociolinguistics; Curriculum; CNPQ::LINGUISTICA, LETRAS E ARTES